The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1038/82521
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptome of Arabidopsis thaliana during systemic acquired resistance

Abstract: Infected plants undergo transcriptional reprogramming during initiation of both local defence and systemic acquired resistance (SAR). We monitored gene-expression changes in Arabidopsis thaliana under 14 different SAR-inducing or SAR-repressing conditions using a DNA microarray representing approximately 25-30% of all A. thaliana genes. We derived groups of genes with common regulation patterns, or regulons. The regulon containing PR-1, a reliable marker gene for SAR in A. thaliana, contains known PR genes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
655
1
20

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 910 publications
(715 citation statements)
references
References 51 publications
24
655
1
20
Order By: Relevance
“…WRKYs are a large family of plant-specific transcription factors that bind to the W-box of promoter regions of many pathogenesis-related genes [35]. Indeed, we observed strong induction of several PR genes.…”
Section: Transcription Factors and The Global Transcriptional Reprogrmentioning
confidence: 54%
“…WRKYs are a large family of plant-specific transcription factors that bind to the W-box of promoter regions of many pathogenesis-related genes [35]. Indeed, we observed strong induction of several PR genes.…”
Section: Transcription Factors and The Global Transcriptional Reprogrmentioning
confidence: 54%
“…This is called the wRKY domain because of the presence of the highly conserved wRKY amino acid sequence (wRKYGQK) also referred to as the "signature sequence" at the N-terminus (Maleck et al 2000;Rushton et al 1996). The wRKY domain is approximately 60 amino acid residues in length with the wRKY signature at the N-terminus and a zinc finger structure at the C-terminus.…”
Section: Wrky Transcription Factors-domain Structure and Bindingmentioning
confidence: 99%
“…Arabidopsis WRKY transcriptional factor (AtWRKY52), containing a LRR motif of TIR-NBS-LRR subclass R gene products, has been shown to enhance disease resistance to several strains of Ralstonia solanacearum [48]. It was also demonstrated that some WRKY genes are necessary for inducible expression of defense-related genes in SAR, such as PR1 in Arabidopsis and PR10 in parsley [49,50]. In Arabidopsis, WRKY29 has been identified as an important downstream component of a MAPK pathway that confers resistance to both bacterial and fungal pathogens [51].…”
Section: Introductionmentioning
confidence: 99%